Does parental mental health moderate the effect of a telephone and internet‐assisted remote parent training for disruptive 4‐year‐old children?. Issue 3 (26th February 2018) - Fossum, Sturla; Cunningham, Charles; Ristkari, Terja; McGrath, Patrick J.; Hinkka‐Yli‐Salomäki, Susanna; Sourander, Andre
Abstract : This study explores the moderators affecting the success of an Internet‐based and telephone assisted remote parent training intervention and compares them to an educational control group. We prospectively identified 464 parents who reported at a health check that their 4‐year‐old children showed elevated levels of externalizing behavior. The moderators explored included parental attention deficit and hyperactivity disorder (ADHD) and parental distress. The dependent variables were child externalization scores and self‐reported parenting skills. The measures were completed at baseline, six and 12‐months follow‐up. The 232 families randomized to active treatment received 11 Internet‐based training sessions with weekly phone calls from a coach. The other 232 families had access to a website that provided general positive parenting advice and one 45‐minute phone‐call from a coach. Using hierarchical linear models, we explored if the parental ADHD or parental distress modified the treatment effects on child externalizing behavior or parenting skills. The results showed that none of the independent variables moderated intervention effects on child externalizing behavior or parenting skills. The lack of significant moderator effects could have been due to the treatment's personalization, the format's flexibility and adaptability to when and how the parents wanted to complete the sessions or the relatively low levels of ADHD and parental distress among the participants.